Interplay between alpha/beta and gamma interferons with B, T, and natural killer cells in the defense against herpes simplex virus type 1 - Vollstedt, Sabine; Arnold, Susi; Schwerdel, Cornelia; Franchini, Marco; Alber, Gottfried; Di Santo, James P; Ackermann, Mathias; Suter, Mark (Journal of virology, 2004)
The essential components of the immune system that control primary and chronic infection with herpes simplex virus type 1 (HSV-1) in mice were investigated. Infection within the first few days can be controlled by alpha/beta interferon (IFN-alpha/beta) alone without significant contribution of B, T, or NK cells. IFN-alpha/beta and IFN-gamma cooperate in the elimination of virus in the absence of these lymphocytes. In contrast, B, T, or NK cells appear to be required to control persistent infection with HSV-1. These results suggest that distinct and essential immune elements are recruited in a time-dependent fashion to control acute and persistent HSV-1 infection.